Biological characterization of adipose‐derived regenerative cells used for the treatment of stress urinary incontinence. (1st December 2020) - Okabe, Yuka Tsukagoshi; Shimizu, Shinobu; Suetake, Yukihiro; Matsui‐Hirai, Hisako; Hasegawa, Shizuka; Takanari, Keisuke; Toriyama, Kazuhiro; Kamei, Yuzuru; Yamamoto, Tokunori; Mizuno, Masaaki; Gotoh, Momokazu
Abstract : Objective: To assess the characteristics of adipose‐derived regenerative cells, and provide supportive data explaining the mechanism of efficacy observed for the use of these cells in the treatment of stress urinary incontinence. Methods: Adipose tissues were harvested by abdominal liposuction from healthy donors and patients with stress urinary incontinence. Adipose‐derived regenerative cells were isolated from tissues using the Celution system, and assessed for their characteristics and ability to differentiate into smooth muscle cells. Results: Adipose‐derived regenerative cells isolated by the Celution system developed into fibroblastic colonies. Flow cytometric analysis of adipose‐derived stem cell markers showed that adipose‐derived regenerative cells were positive for CD34 and CD44, and negative for CD31. Immunofluorescence staining after differentiation showed that colony‐forming cells were positive for alpha‐smooth muscle actin, calponin and desmin, which are smooth muscle cell markers. A cytokine release assay showed that adherent cells secreted cytokines associated with angiogenesis, including vascular endothelial growth factor‐A, angiopoietin‐2 and placental growth factor. Conclusions: Adipose‐derived regenerative cells collected by the Celution system might have clonogenic capacity and an angiogenetic function. These properties might contribute to the mechanisms through which regenerative cell therapy by periurethral injection of autologous adipose‐derived regenerative cells ameliorates stress urinary incontinence.